2017
DOI: 10.1104/pp.17.00411
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed Gene Editing and Protein Overexpression Using a Tobacco mosaic virus Viral Vector

Abstract: Development of CRISPR/Cas9 transient gene editing screening tools in plant biology has been hindered by difficulty of delivering high quantities of biologically active single guide RNAs (sgRNAs). Furthermore, it has been largely accepted that in vivo generated sgRNAs need to be devoid of extraneous nucleotides, which has limited sgRNA expression by delivery vectors. Here, we increased cellular concentrations of sgRNA by transiently delivering sgRNAs using a -derived vector (TRBO) designed with 5' and 3' sgRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
103
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(112 citation statements)
references
References 58 publications
1
103
0
2
Order By: Relevance
“…In previous reports of STU systems for Cas9 in plants, special processing devices, such as the hammerhead ribozyme (Tang et al ) or tRNA element (Ding et al ), was used to release individual sgRNAs. Recently, it was shown that an RNA transcript, consisting of a sgRNA adjoining a GFP protein coding region in the Tobacco mosaic virus , caused target indels and viral‐based GFP overexpression, simultaneously (Cody et al ). Inspired by this finding, we speculated that the Cas9 protein and its sgRNAs may be assembled into a SSTU system, without any additional processing machinery.…”
mentioning
confidence: 99%
“…In previous reports of STU systems for Cas9 in plants, special processing devices, such as the hammerhead ribozyme (Tang et al ) or tRNA element (Ding et al ), was used to release individual sgRNAs. Recently, it was shown that an RNA transcript, consisting of a sgRNA adjoining a GFP protein coding region in the Tobacco mosaic virus , caused target indels and viral‐based GFP overexpression, simultaneously (Cody et al ). Inspired by this finding, we speculated that the Cas9 protein and its sgRNAs may be assembled into a SSTU system, without any additional processing machinery.…”
mentioning
confidence: 99%
“…Two tobraviruses, TRV and PEBV, can be used to edit N. benthamiana and Arabidopsis genes of interest (Ali et al, 2015(Ali et al, , 2018. TMV was also reported to be able to mediate target gene editing in the local leaves by partially substituting the CP ORF with a gRNA (Cody et al, 2017). Very recently, BNYVV has also been used for gRNA delivery in N. benthamiana (Jiang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that viruses can be developed to deliver gRNAs for targeted mutagenesis in plants (Ali et al ., , ; Cody et al ., ; Gil‐Humanes et al ., ; Jiang et al ., ; Yin et al ., ). Compared to the traditional gRNA delivery methods via Agrobacterium transformation, plant virus‐mediated gRNA delivery systems have several advantages: (1) the gRNAs can accumulate to high levels owing to viral replication and systemic spread in plants and may contribute to a higher genome editing efficiency, (2) multiple functional gRNAs can be expressed from a single viral genome, which provides the potential for multi‐targeted genome editing, (3) phenotypic alterations may appear in infected plants in a relatively short period of time after gene targeting by virus‐induced genome editing (VIGE), and (4) transformation and regeneration of agriculturally important crops such as wheat is laborious and time‐consuming, but VIGE may shorten this period and simplify operation and editing processes of a target gene in the specific tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Tobacco Rattle Virus (TRV) [29] and Cabbage Leaf Curl Virus (CaLCuV) [30] have been adapted for this purpose. More recently, Cody et al [31] demonstrated targeted mutagenesis induced by transient expression of Cas9 simultaneous with delivery of sgRNAs from a tobacco mosaic virus-derived vector.…”
Section: Toolkits For Targeted Mutagenesismentioning
confidence: 99%